Quantifying Region-Specific Elastic Properties of Distal Femoral Articular Cartilage: A Shear-Wave Elastography Study. (7th February 2022) - Deng, Weixin; Lin, Ming; Yu, Suiqing; Liang, Hongying; Zhang, Zhijie; Liu, Chunlong
Abstract : Knee osteoarthritis is a disease with the degeneration of articular cartilage as its main feature. Cartilage thickness cannot become a single index to evaluate cartilage degeneration, so it is essential to also evaluate the stiffness. The purposes were as follows: (1) to examine test-retest reliabilities of the elastic modulus measurement in distal femoral articular cartilage (FAC) and compare the changes in specific-regional of distal FAC, (2) to explore the difference in distal FAC stiffness and thickness between the dominant and nondominant sides, and (3) to examine the correlation between the elastic properties of cartilage and the thickness of cartilage. Twenty healthy participants were recruited. The stiffness of distal FAC at the lateral femoral condyle (LFC), medial femoral condyle (MFC), and intercondylar notch (IN) was quantified using shear-wave elastography (SWE). Intra- and interrater reliabilities were excellent for measuring the stiffness of distal FAC (ICC: 0.83-0.98). About a 50% increase in the stiffness of LFC (40.78 kPa) was found when compared with IN (21.82 kPa) and MFC (18.34 kPa). No significant difference was found between the dominant and nondominant sides in distal FAC stiffness and thickness. There was no correlation between the stiffness and thickness of the distal FAC. In conclusion, SWE can quantify the stiffness of the distal FAC.